Disrupting structural violence in South Africa through township tourism. Issue 2 (4th March 2022) - Muldoon, Meghan L.; Mair, Heather L.
Abstract: This paper describes the potential that tourism encounters have in disrupting structural violence (conceptualized as silencing and invisibilization) in South Africa. Based on PhotoVoice research undertaken with a small number of residents of three Cape Town-area townships, we consider how residents' descriptions of their encounters with the tourists can be seen as helping to "polish the wounds of the past" as they shared a sense of being seen and heard. We apply the African philosophical lens of Ubuntu, described by one participant as "I am because we are, " to consider the role of tourism in promoting peace simultaneously at the individual as well as the collective level. While far from unproblematic, this research finds hope in the ways township tourism is disrupting structural violence, thereby supporting the emancipatory aims of post-apartheid South Africa.